Non-governmental organization's contribution to women small-scale farmers: A case study of Tchenzema ward, Morogoro, Tanzania - Massay, Emmanuel Michael; Mujaya, Majio Moshi (Jurnal Sosiologi Dialektika, 2021)
Tanzanian women play a vital role in the country's development and industrialization. Tanzania's agriculture is considered the country's backbone, but women are the driving force behind small-scale farming. This study aims to identify the types of NGOs that support women, small-scale farmers, to investigate the effects of NGOs, and the challenges that small-scale farmers face in Tchenzema ward. The transition and growth model development theory, and patriarchy theory, were used in the study. The study revealed that poor transportation, crop illnesses and insects, lack of pesticides, price fluctuation, lack of energy, and high agricultural equipment prices are some of the issues faced by women small-scale farmers in Tchenzema ward. This study concludes that the lack of collaboration between the Tanzanian government and farmers causes farmers to only rely on NGOs. The government and non-governmental organizations need to support women small-scale farmers so as to solve the challenges, and raising the output, hence let the agriculture sector achieves its national aim of economic growth.